Abemaciclib pharmacology and interactions in the treatment of HR+/HER2− breast cancer: a critical review - Federica Martorana; Maria Vita Sanò; Maria Rosaria Valerio; Stefano Fogli; Paolo Vigneri; Romano Danesi; Vittorio Gebbia (SAGE Publishing, 2024)
Abemaciclib (ABE) in combination with endocrine therapy represents the mainstay treatment for either endocrine-resistant metastatic or high-risk early-stage HR+/HER2− breast cancer patients. Hence, an adequate knowledge of this agent pharmacodynamic, pharmacokinetic, and of its drug-drug interactions (DDIs) is crucial for an optimal patients management. Additionally, ABE interference with food and complementary/alternative medicines should be taken into account in the clinical practice. Several online tools allow to freely check DDIs and can be easily consulted before prescribing ABE. According to one of this instruments, ABE display the lowest number of interactions among the available cyclin-dependent kinase 4/6 inhibitors. Still, clinicians should be aware that online tools cannot replace the technical datasheet of the drug as well as a comprehensive clinical assessment for each patient. Here we critically review the main pharmacological features of ABE, then focusing on its potential interactions with drugs, food, and alternative medicine, in order to provide a guide for its optimal use in the treatment of HR+/HER2− breast cancer patients.